Risk Factors and Perinatal Outcome of Meconium Stained Amniotic Fluid - Chhetri, Uma Devi; Aryal, Shreyashi (Journal of Lumbini Medical College, 2020)
Introduction: Meconium Stained Amniotic Fluid (MSAF) is a frequent finding during deliveries and is a cause for perinatal morbidity and mortality. Meconium Aspiration Syndrome (MAS) in neonates is an association in these deliveries with some infants requiring mechanical ventilation. This study was done with the aim of finding the risk factors for MSAF and its perinatal outcome. Methods: This was a hospital based, cross-sectional study. All the inborn babies delivered with MSAF were included in the study. Antenatal risk factors and perinatal outcomes like mode of delivery, Apgar score, NICU admission and neonatal morbidities mainly MAS were noted. Results: MSAF was seen in 202 (13.6%) neonates out of which 30 (15%)developed MAS. Antenatal risk factors were present in 97 (48%) cases. Mode of delivery was caesarean section in 78 (39%) and instrumental in 25 (13%) cases. Twenty three percent of the neonates required resuscitation at birth while 34% required respiratory support. Morbidities observed were meconium aspiration, pneumonia, septicaemia, perinatal asphyxia, shock, meconium gastritis and persistent pulmonary hypertension. Neonatal mortality amongst all neonates with meconium was 1.5%. Conclusion: Meconium stained amniotic fluid leading to aspiration is a significant cause of neonatal mortality and morbidity. Most of the risk factors for MAS are preventable.